2021
DOI: 10.1016/j.rehab.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different types of exercises on psychological and cognitive features in people with Parkinson's disease: A randomized controlled trial

Abstract: Background: Parkinson's disease (PD) is a neurodegenerative and progressive disease marked by the presence of motor and non-motor symptoms, as psychological and cognitive impairment. Physical exercises have been prescribed as complementary therapy for PD, and the type of intervention and duration of the intervention should be taken into account. Objective: We aimed to compare the effect of different exercise modalities (functional mobility, multimodal and cognitive) and length (4 and 8 months) on psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 48 publications
0
25
0
1
Order By: Relevance
“…In addition, physical exercise interventions for cognition in PD encompass aerobic exercise, but also include resistance training, Tai Chi, dance, physical activity, and physical therapy with or without cognitive training 152153154170214215216229. Finally, although a recent Cochrane review suggested little benefit from combining memantine with ChEIs,230 these data included mainly AD patients and there are plans to specifically evaluate this approach in PDD (NIHR129175).…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…In addition, physical exercise interventions for cognition in PD encompass aerobic exercise, but also include resistance training, Tai Chi, dance, physical activity, and physical therapy with or without cognitive training 152153154170214215216229. Finally, although a recent Cochrane review suggested little benefit from combining memantine with ChEIs,230 these data included mainly AD patients and there are plans to specifically evaluate this approach in PDD (NIHR129175).…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…The 14 studies incorporated in this SR included 1432 participants (Table 2). Of these studies, two were performed in subjects with AD (n = 301) [47][48][49], three studies were carried out with PD (n = 269) patients [50][51][52], and nine studies involved older adults with MCI (n = 862), [53][54][55][56][57][58][59]. The duration of the MEP intervention varied from 24 weeks [48] to 40 weeks [49].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…Of these studies, two were performed in subjects with AD (n = 301) [47][48][49], three studies were carried out with PD (n = 269) patients [50][51][52], and nine studies involved older adults with MCI (n = 862), [53][54][55][56][57][58][59]. The duration of the MEP intervention varied from 24 weeks [48] to 40 weeks [49]. Interventions targeting the comparison or control group varied in content and format.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that an important determinant for a beneficial outcome of physical activity is not just aerobic exercise with minimal cognitive demands but, first and foremost, cognitively enriched aerobic exercise (ie, with cognitive and motor skill component). In this regard, a randomized controlled trial 10 showed that a 32-week intervention requiring both complex locomotor and cognitive exercise can maintain executive features and delay the cognitive decline in PD. These findings are crucial considering that executive dysfunction is frequently present from the early stages of PD.…”
mentioning
confidence: 99%